Developmental parameters of Xylochoris flavipes (Reuter) (Hemiptera: Anthocoridae) fed on life-stages of Rhyzopertha dominica (f.) - Sarker, AC; Islam, W; Parween, S (Journal of Bio-Science, 2019)
The hemipteran predator, Xylocoris flavipes (Reuter) predates the eggs, larvae and pupae of Rhyzopertha dominica (F.) in storage condition and checks their population in considerable level. The nymphs of 1st up to 5th instar and adults of X. flavipes were found efficient to survive on eggs, larvae of 1st up to 4th instar and pupae of R. dominica. The mean duration of developmental period through five nymphal instars on eggs, larvae of 1st up to 4th instars and pupae were 18 ± 1.00, 20 ± 0.58, 16 ± 2.00, 14 ± 1.15, 12 ± 1.15 and 13 ± 0.58 days in R. dominica. The adult female X. flavipes survived longer than the male. Average consumption rates of each nymph of 1st up to 5th instar and adult stage of X. flavipes were found highest on eggs, 1st and 2nd instar larvae but lowest on 4th instar larvae and pupae. The female predator always consumed more individuals than the male. Average survivability rates of nymphs of 1st up to 5th instar and adults were maximum on 1st and 2nd instar larvae and minimum on 4th instar larvae and pupae. The size of the female predator was found larger than the male at all the stages. Based on the ratio 1:1, sex ratio was the best (male and female almost equal in number) on 1st and 2nd instar larvae comparatively than that of other stages. Developmental period, adult longevity, consumption rate, survivability rate, size and sex ratio of X. flavipes were found always significant (p<0.001) in different life stages of R. dominica. This study reveals that mass culture of X. flavipes can be established on R. dominica in the laboratory to get easy and abundant supply of the bug as an agent of biological control. J. bio-sci. 27: 11-21, 2019